A risk management approach to the design of contraceptive implants. Issue 4 (1st October 2010) - Rowlands, Sam; Sujan, Mark-Alexander; Cooke, Matthew
Abstract : This article assesses the risks associated with the insertion and removal of contraceptive implants. Risks to patient safety relate to the way the insertion device is designed and used, rather than to the pharmacological properties of the implant itself. Risks associated with removal are not amenable to thoughtful design. A systems approach is taken, the assumption being that human errors are symptoms of underlying systems deficiencies rather than causes of adverse events. The insertion procedure is broken down into five key steps. Errors in these steps contribute to non-insertion and deep insertion of implants. The design of the Implanon® applicator is critically examined and suggestions made as to how it could be improved in such a way as to reduce errors in its use. The exercise undertaken has coincided with the imminent launch of the redesigned applicator of the new contraceptive implant, Nexplanon®. Preliminary comments are made about the new features of Nexplanon.